Representações da população negra na coleção história, sociedade e cidadania, para o ensino fundamental maior (2017 - 2019) - LIMA , Ivã Dutra (2020)
The present work is an investigation on the representations of the black population in the didactic books of the collection History, society and citizenship, of Alfredo Boulos Júnior, FTD, for the triennium 2017, 2018 and 2019. The central objective is to understand the meanings of the representations of the black population in the collection, since the textbook is a pedagogical tool with a strong presence in the formal Brazilian education system, both in the private and public networks, bearer of the knowledge to be taught in schools in the country, loaded with discourses that in the dialogical relationship with learners can contribute to the constitution of socially diluted values and behavior patterns. As for the specific objectives, we seek to understand the role of the textbook in the Brazilian educational system thinking it as a multifaceted artifact, as it is a product of the publishing world, loaded with discourse, but also a commercial product, being a profitable business for publishers . Another important point was to analyze the public policies for the textbook, with emphasis on the National Textbook Program, PNLD, focusing on state actions historically undertaken with the purpose of controlling, via legal ties, not only the distribution of such pedagogical artifacts, but his speeches as a place of speech. We seek to understand the importance of black social movements, like the Black Movement, for their role in historical struggles for the structuring of an anti-racist society. As a practical example of this historic struggle we have Law 10.639 / 2003, which made the teaching of Afro-Brazilian and African history and culture mandatory in all schools, public and private, in elementary and high school. We also aim to understand the meanings of representations about the black population when analyzing the iconographic and textual contribution of the collection. Within the scope of the methodology, we chose to analyze the iconographic contribution and the textual contribution of the collection, and in the case of the analysis of the iconographic contribution we divided into categories: family relationships, world of work, material / immaterial culture, playful universe and political universe . Regarding the textual contribution, we analyze the books by series: 6th year, 7th year, 8th year and 9th year. The result of this methodological approach was the intersection of narratives about Africa and Afro-descendants, apprehending the meanings of representations about the black population present in the books of the collection. We can conclude that the inclusion of the mentioned theme in textbooks constitutes an important step towards guiding the structuring of a society that values the African cultural matrix, but there are still flaws to be corrected, such as the necessary problematization of the population's struggles black for recognition and appreciation of its importance in the formation process of Brazilian society. These are fundamental debates so that the student body can effectively have a positive perception about Africa and people of African descent. Finally, we understand that we can add value to discussions about the racial issue in vogue in Brazil.